An Analysis of Oral Academic Discourse in Classroom Discussions - Russel J. Aporbo (East Asian Journal of Multidisciplinary Research, 2023)
This discourse analysis is aimed  to investigate the what sorts of speech acts have illocutionary power in constructing academic discussions and the ways speech acts such as disagreements framed and organized such as in turn-taking in oral academic discussions and  how face threatening and maintaining self- mage are conceptualized. This includes thirty minutes conversation between the instructor and her students in a classroom setting. The nature of interaction from the verbal exchanges in academic discussions were examined, analyzed and clarified based on the Speech Act Theory of Austin and Searle, Frame Theory of Goffman and Tannen and lastly, Politeness Theory of Brown and Levinson.  The results showed that the sorts of speech acts have illocutionary power in constructing academic discussions and there are ways that  speech acts such as disagreements are framed and organized such as in turn-taking in oral academic discussions in order to maintain the social image of  the participants of conversation. Verbal interaction at discussions has its way in maintaining the face-work like threatening and displaying positive image. The aspects of face as basic wants are composed of negative and positive faces are applied to acts threatening positive or negative face, and the three variables are - power, social distance and imposition can be applied in just a small segment of conversation. It was revealed that keying’ which consists of an “openly admitted” transformation of untransformed activity and concerns a systematic reworking of